Clean Synthesis of an Economical 3D Nanochain Network of PdCu Alloy with Enhanced Electrocatalytic Performance towards Ethanol Oxidation. Issue 49 (16th October 2015) - Liu, Jiawei; Huang, Zhao; Cai, Kai; Zhang, Huan; Lu, Zhicheng; Li, Tingting; Zuo, Yunpeng; Han, Heyou
Abstract: A one‐pot method for the fast synthesis of a 3D nanochain network (NNC) of PdCu alloy without any surfactants is described. The composition of the as‐prepared PdCu alloy catalysts can be precisely controlled by changing the precursor ratio of Pd to Cu. First, the Cu content changes the electronic structure of Pd in the 3D NNC of PdCu alloy. Second, the 3D network structure offers large open pores, high surface areas, and self‐supported properties. Third, the surfactant‐free strategy results in a relatively clean surface. These factors all contribute to better electrocatalytic activity and durability towards ethanol oxidation. Moreover, the use of copper in the alloy lowers the price of the catalyst by replacing the noble metal palladium with non‐noble metal copper. The composition‐optimized Pd80 Cu20 alloy in the 3D NNC catalyst shows an increased electrochemically active surface area (80.95 m 2 g −1 ) and a 3.62‐fold enhancement of mass activity (6.16 A mg −1 ) over a commercial Pd/C catalyst. Abstract : Non‐noble alloying : The efficient synthesis of an economical PdCu 3D nanochain network (NNC) is accomplished by a surfactant‐free method. The composition‐optimized Pd80 Cu20 3D NNC catalyst showed an increased electrochemically active surface area and mass activity over a commercial Pd/C catalyst.